Presence of Immune Complexes of IgG/IgM Bound to B2-glycoprotein I Is Associated With Non-criteria Clinical Manifestations in Patients With Antiphospholipid Syndrome - Pérez, Dolores; Stojanovich, Ljudmila; Naranjo, Laura; Stanisavljevic, Natasa; Bogdanovic, Gordana; Serrano, Manuel; Serrano, Antonio (Frontiers in Immunology, 2018)
Background. Antiphospholipid syndrome (APS) is an acquired autoimmune disorder defined by the presence of both clinical (thromboembolic events or pregnancy morbidity) and laboratory (antiphospholipid antibodies, aPL) manifestations. Despite their importance, several clinical manifestations strongly associated with APS such as livedo reticularis (LR), thrombocytopenia, sicca-ophthalmic(sicca), heart or neurological manifestations are not included in the APS clinical classification criteria. Circulating immune complexes (CIC) formed by Beta-2-glycoprotein I (B2GPI) and aPL (B2-CIC) have been described and their presence has been related with thrombotic events. Methods. Cross-sectional and observational cohort study in APS patients with thrombotic symptomatology. Setting and Participants Fifty-seven patients from the University Hospital Center Bezanijska Kosa (Belgrade, Serbia) who met the APS classification criteria (35 with primary APS and 22 with APS associated to systemic lupus erythematosus). This study aimed to determine the prevalence of B2-CIC in APS patients and to evaluate their association with clinical manifestations of APS not included in the classification criteria. Results B2-CIC prevalence in APS patients was 19.3%. The presence of thrombocytopenia (OR:5.7), livedo reticularis (OR:5.6), sicca (OR:12.6) and leukopenia (OR:5.6) was significantly higher in patients with B2-CIC than in the rest of APS patients. C3 and C4 complement factor levels were significantly lower in B2-CIC positive patients, which suggests a greater consumption of complement. Patients with quadruple aPL positivity (triple aPL-positivity plus the presence of B2-CIC) showed a higher prevalence of thrombocytopenia, leucopenia and LR than those with single/double aPL-positivity. No significant differences were found in the frequencies observed in patients with triple-only vs single/double aPL-positivity. There were no significant differences between patients with primary APS and lupus-associated APS regarding the prevalence of B2-CIC and outcomes. Conclusions Presence of B2-CIC is strongly associated with several non-criteria clinical manifestations related to APS and to higher complement consumption. More studies are required to better understand the clinical significance of B2-CIC.